Hybrid Block Copolymer/Perovskite Heterointerfaces for Efficient Solar Cells. Issue 1 (23rd November 2022) - Sun, Jianguo; Li, Bin; Hu, Long; Guo, Junjun; Ling, Xufeng; Zhang, Xuliang; Zhang, Chi; Wu, Xianxin; Huang, Hehe; Han, Chenxu; Liu, Xinfeng; Li, Youyong; et al.
Abstract: Solution processable semiconductors like organics and emerging lead halide perovskites (LHPs) are ideal candidates for photovoltaics combining high performance and flexibility with reduced manufacturing cost. Moreover, the study of hybrid semiconductors would lead to advanced structures and deep understanding that will propel this field even further. Herein, a novel device architecture involving block copolymer/perovskite hybrid bulk heterointerfaces is investigated, such a modification could enhance light absorption, create an energy level cascade, and provides a thin hydrophobic layer, thus enabling enhanced carrier generation, promoting energy transfer and preventing moisture invasion, respectively. The resulting hybrid block copolymer/perovskite solar cell exhibits a champion efficiency of 24.07% for 0.0725 cm 2 ‐sized devices and 21.44% for 1 cm 2 ‐sized devices, respectively, together with enhanced stability, which is among the highest reports of organic/perovskite hybrid devices. More importantly, this approach has been effectively extended to other LHPs with different chemical compositions like MAPbI3 and CsPbI3, which may shed light on the design of highly efficient block copolymer/perovskite hybrid materials and architectures that would overcome current limitations for realistic application exploration. Abstract : A hybrid block copolymer/perovskite heterointerfaces strategy is developed for the first time by introducing a novel and functional block copolymer PBDB‐T‐ b ‐PTY6, and consequently, such an architecture enhances light harvesting, promotes charge transfer and prevents moisture invasion, delivering a champion efficiency over 24% together with enhanced stability.